Prevalencia y factores de la anemia ferropénica en niños menores de cinco años del Centro de Salud N°1 - Feijoo Velepucha, Álvaro Steven (2023)
Low iron levels are an important cause of declining levels of cognitive care, reduced mental lucidity and learning problems. This study was conducted at the Number 1 Health Center in Loja City and was aimed at analysing the prevalence and associated factors of anemia ferropenic in children under five years of age. The research consisted of a population of 1 258 patients under five who were treated during 2021, where 23.53% (296) were children under five years of age diagnosed with anemia, of whom 151 were males and 145 women. It was descriptive, documentary, and quantitative approach, realized through the collection of statistical data from the Health Care Registration Platform (PRAS). The prevalence of ferropenic anemia among the population who went to Health Center No. 1 during 2021 were children under 1 year of age, revealing that this age group is beginning to have problems with their normal development, even though they are still in breastfeeding. The greatest incidence in this group is explained by the iron imbalance resulting from the growth demand that exceeds the iron inputs found in food ingested daily. In view of this research, it is recommended that iron deficit be prevented in order to avoid systemic manifestations and anemia, and that breastfeeding should be encouraged with nutritional supplements from 6 months of age